Tanzania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
This Selected Issues paper reviews developments in Tanzania in the main fiscal indicators and related structural reforms to explain the success in fiscal management. The paper contains a brief overview of the structure of the public sector. Main developments in revenue and expenditure are covered. The paper concludes that the rationalization of expenditure programs and the progressive shift from domestic to foreign financing were at the core of Tanzanian macroeconomic stabilization in the second half of the 1990s, contributing to a sharp reduction in inflation.